PARENT EDUCATION INTERVENTION RESULTS IN DECREASED CHALLENGING BEHAVIOR AND IMPROVED TASK ENGAGEMENT FOR STUDENTS WITH DISABILITIES DURING ACADEMIC TASKS. (16th August 2013) - Lequia, Jenna; Machalicek, Wendy; Lyons, Gregory
<x xml:space="preserve">Abstract</x> Children with developmental disabilities and attention deficit hyperactivity disorder often engage in challenging behavior when presented with academic demands. Parents of school‐age children with such diagnoses are commonly asked to assist their child with academic tasks but may struggle to do so as a result of challenging behavior. This study evaluated the effects of a parent education intervention on the challenging behaviors and task engagement of three school‐age children with disabilities during academic activities. Parent education consisted of (i) weekly didactic instruction; (ii) modeling; (iii) role‐play; and (iv) in vivo coaching and performance feedback. Using a non‐concurrent multiple baseline across participants with embedded individual multi‐element design, this study demonstrates that a parent education intervention results in decreases in challenging behavior and increases in task engagement. These results suggest that parent education focused on addressing challenging behavior during one‐to‐one instruction may facilitate completion of academic tasks. Implications for practice and suggestions for future research are discussed. Copyright © 2013 John Wiley & Sons, Ltd.